The potential impacts of COVID-19 pandemic on international defense and security (Revista da Escola de Guerra Naval, 2023)
The world is struggling with the widely spread effects of thevirus Covid-19. The damage until now took more than a millionpeople in less than a year, which is more than a considerablynumber of small wars together. The purpose of this article isto identify signs, uncertainties and trends from future studiesthat have been written in the last few months by governmentagencies, large private companies, academic institutions andworldwide organizations about the influence of the pandemicin areas such as economy, international relations, geopolitics,environment, technology and society in order to assess those ofmain potential impacts for national defense and internationalsecurity. The methodology relied on semantic analysisapplication based on 55 selected futures studies (reports,papers, books etc.) written in three largely spoken languagesregarding both Covid-19 and prospective scenarios. Theanalysis focus on the complex tangle between technology andsociety, as well as, between politics and economy. The resultsare summarized in a list of variables of trend or uncertaintiesfollowed by some possible impacts on how they can interactor affect the issue. This paper points out the necessity to lookover this pandemic horizon with contributions from differentgovernment departments, think tanks, academics and non-governmental organizations to short the time-lapse betweenthe strategic formulation and its results.